(untitled) (Research, Society and Development, 2022)
Objectives: The objective of this research is to identify the perceptions of health professionals about early diagnosis and communicational and relational skills in the care of children with Autism Spectrum Disorder. Methodology: Cross-sectional, qualitative study with health professionals who care for patients with Autistic Spectrum Disorder, residing in Itajubá-MG. Data were analyzed according to Bardin’s content analysis methodology. Results: Six central themes were found about the perceptions of health professionals about early diagnosis and communication and relational skills in the care of children with Autism Spectrum Disorder: Benefits of early diagnosis: better clinical evolution (100%); Relevance of foster care in the treatment of ASD (100%); Challenges in the interaction between health professionals and patients: communication strategies (91.6%); Competences and abilities in the health professional/patient relationship: empathy (75%); Privileged diagnostic signs: developmental delays (66.6%); Challenges for the feasibility of treatment with the multidisciplinary team (66.6%). Conclusion: It was possible to show that the great benefit of early ASD diagnosis is the better clinical evolution of the autistic patient, being possible to work on strategies that favor communication and the individual’s integral development.